2020
DOI: 10.1519/jsc.0000000000002982
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Joint Isokinetic Dynamometry: A Critical Review

Abstract: Dvir, Z and Müller, S. Multiple-joint isokinetic dynamometry: a critical review. J Strength Cond Res 34(2): 587–601, 2020—Angular isokinetic dynamometry (AID) is widely regarded as the gold standard for dynamic muscle performance testing. Based on the rotational movement of its actuator, AID targets “single-joint” (knee, shoulder, hip, etc.) configurations namely measurement of muscle potential while it moves the lever arm-limb assembly ostensibly around a single fixed axis. On the other hand, the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 35 publications
2
34
0
5
Order By: Relevance
“…Until now, the evaluation of trunk strength has been carried out by way of medicine-ball throws (Glenn et al, 2015), handheld dynamometers (Cowley et al, 2009; Paalanne et al, 2009; Newman, Pollock & Hunt, 2012) or isokinetic devices (Dervisevic, Hadzic & Burger, 2007; Mcintire et al, 2007; Roth et al, 2017). In these isokinetic devices, there is no evaluation protocol to know at what velocity and at what range of movement the evaluation should be performed (Dvir & Müller, 2019), even though there have been attempts (Dvir & Keating, 2001). Still, there are indications that low-velocity movements are more reliable for measuring trunk strength (Guilhem et al, 2014; Roth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the evaluation of trunk strength has been carried out by way of medicine-ball throws (Glenn et al, 2015), handheld dynamometers (Cowley et al, 2009; Paalanne et al, 2009; Newman, Pollock & Hunt, 2012) or isokinetic devices (Dervisevic, Hadzic & Burger, 2007; Mcintire et al, 2007; Roth et al, 2017). In these isokinetic devices, there is no evaluation protocol to know at what velocity and at what range of movement the evaluation should be performed (Dvir & Müller, 2019), even though there have been attempts (Dvir & Keating, 2001). Still, there are indications that low-velocity movements are more reliable for measuring trunk strength (Guilhem et al, 2014; Roth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Isokinetic dynamometry is considered the gold standard for dynamic muscle performance testing [28,29]; thus, clinicians and researchers should be encouraged to use this device to conduct their physical function evaluations. Previous studies have reported the test-retest reliability of isokinetic measures in several populations different from patients undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another option to evaluate the different types of muscle contractions includes angular isokinetic dynamometers (AID). Which are recognized as the gold standard for evaluating the eccentric strength of the knee flexor muscles, but lack practical utility in comparison with other devices (Opar et al, 2013a;Van Dyk, Witvrouw & Bahr, 2018;Dvir & Muller, 2019). AIDs, like the NHE, do not have transference to the actual playing actions that occur during the injury mechanism in soccer players, as the movement is focused only on the knee joint while the hip remains static throughout the entire run (Bourne et al, 2018).…”
Section: Introductionmentioning
confidence: 99%